2007
DOI: 10.1289/ehp.9882
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Urinary Phthalate Metabolites Are Associated with Increased Waist Circumference and Insulin Resistance in Adult U.S. Males

Abstract: BackgroundPhthalates impair rodent testicular function and have been associated with anti-androgenic effects in humans, including decreased testosterone levels. Low testosterone in adult human males has been associated with increased prevalence of obesity, insulin resistance, and diabetes.ObjectivesOur objective in this study was to investigate phthalate exposure and its associations with abdominal obesity and insulin resistance.MethodsSubjects were adult U.S. male participants in the National Health and Nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
364
8
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 571 publications
(393 citation statements)
references
References 68 publications
16
364
8
5
Order By: Relevance
“…Finally, we showed that DEHP dose-dependently induce the expression of the CAR target gene CYP2B6 in primary human hepatocytes. This original finding is discussed in view of the crucial role played by the liver in controlling energy homeostasis and the recent findings which associate phthalate exposure to the onset of the metabolic syndrome in men [18,19].…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Finally, we showed that DEHP dose-dependently induce the expression of the CAR target gene CYP2B6 in primary human hepatocytes. This original finding is discussed in view of the crucial role played by the liver in controlling energy homeostasis and the recent findings which associate phthalate exposure to the onset of the metabolic syndrome in men [18,19].…”
Section: Introductionmentioning
confidence: 91%
“…In mammals, including humans, phthalate exposure is associated with endocrine disruption [15][16][17] and metabolic disorders [18,19]. In rodents, in utero exposure to phthalates results in developmental and reproductive defects similar to those termed testicular dysgenesis syndrome in humans [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In short-and long-term rodent studies, dose-related adverse effects, such as deregulated levels of serum insulin, blood glucose, liver glycogen, T3, T4 and thyroid stimulating hormone as well as cortisol, were observed. 19,20 Even more specifically, Stahlhut et al 21 showed that the log-transformed concentrations of several phthalate metabolites positively correlated with abdominal obesity and insulin resistance in adult US males.…”
Section: Phthalates and Metabolic Disruptionmentioning
confidence: 99%